Elastin‐like recombinamers with acquired functionalities for gene‐delivery applications. Issue 10 (27th March 2015) - Piña, Maria J.; Alex, Susan M.; Arias, Francisco J.; Santos, Mercedes; Rodriguez‐Cabello, Jose C.; Ramesan, Rekha M.; Sharma, Chandra P.
Abstract In this work, well‐defined elastin‐like recombinamers (ELRs) were studied as a choice to the existing nonviral vectors due to their biocompatibility and ease of scale‐up. Functional motifs, namely penetratin and LAEL fusogenic peptides were incorporated into a basic ELR sequence, and imidazole groups were subsequently covalently bound obtaining ELRs with new functionalities. Stable polyplexes composed of plasmid DNA and ELRs were formed. A particle size around 200 nm and a zeta potential up to nearly +24 mV made them suitable for gene delivery purposes. Additionally, viability and transfection assays with C6 rat glioma cell line showed an increase in the cellular uptake and transfection levels for the construction containing the LAEL motif. This study highlights the importance of controlling the polymer functionality using recombinant techniques and establishes the utility of ELRs as biocompatible nonviral systems for gene‐therapy applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3166–3178, 2015.